Instructional Media Innovation: A Web-Based Digital Dictionary for Karate Terminology - Rudiyanto Rudiyanto; Aidilla Pratiwi Siregar; M.Fadlin Al-Farhan's; Intan Permata Sari br Saragih; Enggellina Gori (IGI in Education Insight, 2026)
Introduction: The integration of karate as a competitive sport and physical education discipline in higher education curricula presents significant pedagogical challenges, particularly in the domain of specialised Japanese-origin terminology. Students in physical education programmes frequently encounter difficulties in comprehending, correctly pronouncing, and applying karate-specific vocabulary, which impedes their overall learning progression and technical skill acquisition. Purpose of the study: This study aimed to develop, validate, and evaluate the feasibility of a web-based digital dictionary for karate terminology as an innovative instructional media tool for undergraduate students enrolled in physical education programmes. Materials and Methods: An educational Research and Development (R&D) methodology was employed using the ADDIE instructional design model (Analysis, Design, Development, Implementation, Evaluation). Participants comprised 30 undergraduate students from the Physical Education Study Programme at Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, Indonesia, and two expert validators (one karate content expert; one instructional media expert). Data were collected using structured Likert-scale questionnaires and analysed through percentage-based feasibility assessment. Results: Expert validation yielded feasibility scores of 87.5% for content validity and 90.0% for media design quality, both classified as "Very Feasible." Student response assessments from small-group (n = 10) and large-group (n = 30) trials yielded mean percentage scores of 84.2% and 87.6%, respectively, both categorised as "Very Feasible." The overall composite feasibility score was 87.3%. Conclusions: The web-based digital dictionary for karate terminology demonstrated high feasibility as an instructional media innovation. The product effectively supports undergraduate students’ comprehension of karate terminology and is recommended for systematic integration into physical education curricula.